Awareness and management of menstrual hygiene practices in adolescent girls - Sunil, Krupa Ann; John, Agatha Mary; Saji, Angitha; B., Abhilash Kumar; Thomas, Abel Abraham (International Journal Of Community Medicine And Public Health, 2021)
Background: Menstruation is a natural part of the female reproductive cycle in which periodic discharge of blood from the uterus exits through the vagina. Menstruation is also surrounded with social taboos and supernatural beliefs. The poor knowledge and understanding of menstruation may lead to unsafe hygienic practice that in turn increases the risk of reproductive and genito-urinary tract infections and leads to overall poor quality of life. The aim of this study was to compare the awareness about menstrual hygiene management among adolescent girls along with objectives of evaluation of menstrual hygiene practices. Methods: The study was a prospective observational study done with a sample size of 650 subjects of 9 to 18 age group in whom menstruation already occurred who were recruited from five different schools in regions of Pathanamthitta and Alappuzha. The study was conducted in 3 phases, where initially a pre designed well-structured questionnaire was provided to assess the attitude, awareness and practices. Results: The results obtained described that the subjects had better knowledge and positive attitude regarding menstruation and hygiene practices when compared to subjects from other regions of India but still they lacked some adequate and updated information on menstruation. Conclusions: This study paved a way for discussion on menstruation to the adolescent girls, providing them the information they lacked and a better guidance.